The influence of interaction in the «teacher-pupil» system on schoolchildren’s learning and development (based on foreign publications) - Fomichenko, A.S. (Sovremennaâ Zarubežnaâ Psihologiâ, 2019)
This article is devoted to the description of the influence of the teacher-pupils’ relationship on schoolchildren’s learning and development. Factual material is presented in favor of the fundamental importance of favorable interpersonal relations between the teacher and pupils. The problem of a negative relationship, its negative impact on academic performance, pupils’ behavior, their attitude to the learning process, peers, teachers and the school as a whole are analyzed in detail. This study demonstrates the relationship between teachers’ mental representations about the relationship in the teacher-pupil system and teacher behavior Данная статья посвящена описанию особенностей влияния характера взаимоотношений в системе «учитель-ученик» на процессы обучения и развития школьников. Представлен фактический успеваемость, поведение учеников, их отношение к процессу обучения материал в пользу основополагающего значения благоприятных межличностных связей учителя с учащимися. Детально анализируются проблемные взаимодействия в этой сфере, их отрицательное влияние на академическую, сверстникам, учителям и школе в целом. Демонстрируется связь между ментальными представлениями и реальным поведением учителей во взаимоотношениях «учитель-ученик»